An Impedance Humidity Sensor Based on CVD Grown WSe2 2D Films - Bhadra, Jolly; Sassi, Lucas M.; Oliveira, Eliezer Fernando [UNESP]; Hachtel, Jordan A.; Parangusan, Hemalatha; Mallick, Shoaib Alam; Ahmad, Zubair; Galvao, Douglas S.; Puthirath, Anand B.; Vajtai, Robert; Ajayan, Pulickel M.; Al-Thani, Noora (American Chemical Society (ACS), 2024)
2D materials-based planar devices have been sought after for gas and humidity sensor applications owing to their high sensitivity due to their ultrathin nature and increased surface area. Herein, 2D WSe2 films-based planner devices were fabricated to evaluate their performance for potential application in humidity sensors. The structure and morphology of the WSe2 sensing films were studied by Raman spectroscopy, photoluminescence, optical microscopy, and scanning electron microscopy (SEM) techniques. The relative humidity-dependent sensing performances of the 2D WSe2 films were evaluated using current-voltage (I-V), relative impedance, and complex total impedance (electrochemical impedance spectroscopy, EIS) techniques. This sensor showed a very stable and repeatable performance investigated over the period of 18 months. The response and recovery times of the WSe2-based impedance sensors were found to be 40 and 30 s, respectively. The WSe2 sensor exhibits a 2 ± 1% minimum hysteresis at a lower humidity level (50% RH) and around 8 ± 2% maximum hysteresis at relative humidity level (70% RH). This value of hysteresis is in the acceptable range during the initial investigation of any material to explore its potential for application in humidity sensors. The density functional theory (DFT) analysis was performed with the interaction from water molecules of the WSe2 sample for a better understanding of the sensing mechanism of devices.
Keywords: 2D- WSe2; Chemical vapor deposition (CVD); Density functional theory (DFT); Humidity sensor; Impedance humidity sensor; Response and recovery times; Sensitivity